Thermoluminescence characteristics of silicon optical fibre doped with ytterbium and ytterbium - terbium as photon dosimeter [electronic resource] - Mohd. Hilmi Sahini, 1989- author; Husin Wagiran, supervisor; Alam Saeed, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014